2000
DOI: 10.1046/j.1365-2141.2000.02341.x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of natural killer cells and T cells by analysis of BCR-ABL rearrangement from patients with chronic myelogenous leukaemia

Abstract: Chronic myelogenous leukaemia (CML) is a haematological malignant disorder characterized by the Philadelphia chromosome (Ph) and BCR-ABL gene rearrangement. This abnormal fusion gene can be considered to serve as a marker for the transformed cell clone in CML and is found in all cells arising from the same malignant precursor cell. It has been detected in CML cells of the myeloid, monocytic, erythroid and B-lymphocytic lineages. However, it is still arguable as to whether T lymphocytes or natural killer (NK) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Overall, our results confirmed the involvement of the neutrophil, monocytic, eosinophil, erythroid, and CD34 HPC cells in virtually all BCR/ABL + CML patients; interestingly, no significant differences were found between m BCR/ABL + and M BCR/ABL + cases with regard to the pattern of involvement of myeloid cells. Regarding lymphoid cells, variable patterns of BCR/ABL involvement were detected, in line with previous reports (MacKinney et al , 1993; al Amin et al , 1998; Takahashi et al , 1998; Cho et al , 2000; Nakajima et al , 2002). A more detailed analysis of the different lymphoid populations showed that B‐ and NK‐cells were more frequently involved, while BCR/ABL + T‐cells were only seldomly detected.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, our results confirmed the involvement of the neutrophil, monocytic, eosinophil, erythroid, and CD34 HPC cells in virtually all BCR/ABL + CML patients; interestingly, no significant differences were found between m BCR/ABL + and M BCR/ABL + cases with regard to the pattern of involvement of myeloid cells. Regarding lymphoid cells, variable patterns of BCR/ABL involvement were detected, in line with previous reports (MacKinney et al , 1993; al Amin et al , 1998; Takahashi et al , 1998; Cho et al , 2000; Nakajima et al , 2002). A more detailed analysis of the different lymphoid populations showed that B‐ and NK‐cells were more frequently involved, while BCR/ABL + T‐cells were only seldomly detected.…”
Section: Discussionsupporting
confidence: 90%
“…Despite this, the involvement of mature cells from some haematopoietic lymphoid lineages, particularly T‐ and natural killer (NK)‐cells, remains controversial. Accordingly, while the presence of the Ph‐chromosome has been reported in a small fraction of mature T‐ and B‐lymphocytes as well as NK‐cells in some CML cases (MacKinney et al , 1993; al Amin et al , 1998; Takahashi et al , 1998; Cho et al , 2000; Nakajima et al , 2002), a great variability exists regarding the frequency of involvement of these cell populations.…”
mentioning
confidence: 99%
“…As nilotinib might be used in the framework of allo‐transplantation and other T cell‐based immunotherapies, we wondered whether inhibition of ABL kinase by nilotinib might have a detrimental effect on the immune response. In several studies, T lymphocytes from CML patients have been found to be Ph chromosome negative and/or BCR‐ABL negative [35–37]. On the other hand, several of intracellular signalling molecules triggered by the ABL kinase are also involved in the activation pathways of immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…The results hereby obtained, indicate that in patients with CML a very small proportion of T and NK lymphocytes at diagnosis is capable of producing cytokines, indicating that the lymphoid population shows important functional defects. These defects appear related to the effects exerted by CML cells rather than by the disease itself, because it has been demonstrated that both NK and T cells do not belong to the bcr/abl‐positive clone (Cho et al , 2000). However, such profound deficiencies are not irreversible and may be reversed during the remission phase of the disease.…”
Section: Discussionmentioning
confidence: 99%